Método RAWS/RAW para estimaç\~ao anual da matriz de insumo-produto na referência 2000 das contas nacionais - Thiago Sevilhano Martinez (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– The aim of this paper is to build the so-called RAWS/RAW method to estimate an annual series of Input-Output Tables (IOTs) in 2000 reference of Brazilian national accounts. The RAWS/RAW differs from other procedures applied to Brazil in that it is based on algorithms that optimize the use of relevant information available. We develop the RAW algorithm from the RAWS algorithm presented in AUTORX (2013), by incorporating both its methodological advances and auxiliary tables of the 2000/2005 IOTs estimated there. Using the 2000 and 2005 IOTs obtained from the RAWS algorithm, we both interpolate 2001-2004 IOTs and project 2006-2009 IOTs with the RAW algorithm. To test the RAWS/RAW method, we project a version of the 2005 IOT using information from the 2000 IOT, which, according to various measures of accuracy, outperforms Guilhoto and Sesso-Filho (2005, 2010) in comparison with the 2005 IOT released by IBGE.
Keywords: D57; C67; E01; 330; input-output; National Accounts; RAS; matrix balancing; State